Social and Environmental Responsibility in Academic Education - Ísper Garbin, Artênio José; Mendes de Paula Gomes, Adrielle; Perez de Souza, Maria; Moreira Arcieri, Renato; Adas Saliba Rovida, Tânia; Adas Saliba Garbin, Cléa (O Mundo da Saúde, 2015)
Health professionals should be concerned with the waste generated by their activities, and develop specific abilities and skills since graduation, requiring the same conscious positioning and willingness to collaborate in finding solutions. Verify the knowledge of dental undergraduate students of a Public Faculty in the State of São Paulo who were in clinical activity in the first half of 2012 about waste management of health service. We performed a cross-sectional descriptive study. The data collection instrument was a self-administered questionnaire, and after the collection was made tabulating the results through the Epi Info 6.04. Values ere expressed by means of frequency in the form of graphs and tables. Of the 140 aca- demic participants, the majority (96.4%) claims to know what RSS is. However, 45.7% answered incorrectly about disposing waste group A (suction system and gloves infected) and 6.4% on the disposal of the group E (sharps waste). Regarding the developer and fixer solutions and lead blades of the dental X-rays, 30% and 48.6%, respectively, not answered correctly. It is concluded that the knowledge of the students on the theme is still flawed, reflecting the need of teaching methodologies seek ways to sensitize future professionals, so that they develop a sense of responsibility and ethical commitment to the health of society and the environment.